2015
DOI: 10.1002/bio.2949
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence properties of gamma‐irradiated nano‐structure hydroxyapatite

Abstract: The suitability of nano-structured hydroxyapatite (HAP) for use as a thermoluminescence dosimeter was investigated. HAP samples were synthesized using a hydrolysis method. The formation of nanoparticles was confirmed by X-ray diffraction and average particle size was estimated to be ~30 nm. The glow curve exhibited a peak centered at around 200 °C. The additive dose method was applied and this showed that the thermoluminescence (TL) glow curves follow first-order kinetics due to the non-shifting nature of Tm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[88][89][90] FOM was also obtained as less than 3.0% for the deconvoluted glow curves, which meant that the fits were good. [21,91,92] Figures 18 and 19 show the deconvolution graphs of two optimal samples.…”
Section: Geometric and Kinetic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…[88][89][90] FOM was also obtained as less than 3.0% for the deconvoluted glow curves, which meant that the fits were good. [21,91,92] Figures 18 and 19 show the deconvolution graphs of two optimal samples.…”
Section: Geometric and Kinetic Parametersmentioning
confidence: 99%
“…[ 2,3,18,19 ] HAP has excellent importance in potential medical applications due to its characteristics such as biocompatibility, and bioactivity and flexible structure. [ 4,20,21 ] It is also used as an implant in hard tissue replacement and for manufacturing prostheses to compensate the various types of defects. Due to the high adsorption, it is used as an absorbent and identifier of toxic compounds and metals in water.…”
Section: Introductionmentioning
confidence: 99%
“…As far as individual studies on doping CP with luminescent ions are concerned, they will be briefly reviewed here. For instance, it was demonstrated that HAp:Gd 3+ nanoparticles obtained through hydrothermal processing exhibit a strongly linear dependence of luminescence responses on the radiation dose of gamma rays due to which they could be used in thermoluminescence dosimetry 27 . Similarly, 159 Gd-doped HAp nanorods synthesized as a carrier for radioisotopes were suitable for the detection and treatment of osteosarcoma using magnetic resonance imaging and production of 159 Gd-32 P-HAp caused by neutron activation 28 .…”
mentioning
confidence: 99%